2024
DOI: 10.3390/catal14030160
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Catalytic Synthesis of Bioactive Compounds in Natural Deep Eutectic Solvents (NADESs): A Survey across the Catalytic Spectrum

Elisabete P. Carreiro,
Hans-Jürgen Federsel,
Gesine J. Hermann
et al.

Abstract: Deep eutectic solvents (DESs) are a mixture of two or more components, and at a particular composition, they become liquids at room temperature. When the compounds that constitute the DESs are primary metabolites namely, amino acids, organic acids, sugars, or choline derivatives, the DESs are called natural deep eutectic solvents (NADESs). NADESs fully represent green chemistry principles. These solvents are highly welcome, as they are obtained from renewable resources, and gratifyingly are biodegradable and b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Instead of using the standard choline chloride with urea and glycerol, we opted to use betaine (trimethylglycine) and some simple C5- and C6-sugars. We studied the benchmark Michael additions described above with the nonimmobilized Rawal catalyst, and obtained excellent results, in terms of yields, stereoselectivities, and recovery. , We investigated three types of betaine-based DESs with three different sugars: d -sorbitol, d -xylitol, and d -mannitol ( D Figure ). We found that the d -sorbitol-based DES was the best performer, and we could carry out multiple cycles at catalyst loadings of 1 and 5% (up to 10 cycles in the case of methyl 2-oxocyclopentane-1-carboxylate, achieving a yield of 97%, ee of 93% and de of 97% on the 10th cycle).…”
Section: Cinchona Catalysts – For Asymmetric Organocatalysismentioning
confidence: 99%
“…Instead of using the standard choline chloride with urea and glycerol, we opted to use betaine (trimethylglycine) and some simple C5- and C6-sugars. We studied the benchmark Michael additions described above with the nonimmobilized Rawal catalyst, and obtained excellent results, in terms of yields, stereoselectivities, and recovery. , We investigated three types of betaine-based DESs with three different sugars: d -sorbitol, d -xylitol, and d -mannitol ( D Figure ). We found that the d -sorbitol-based DES was the best performer, and we could carry out multiple cycles at catalyst loadings of 1 and 5% (up to 10 cycles in the case of methyl 2-oxocyclopentane-1-carboxylate, achieving a yield of 97%, ee of 93% and de of 97% on the 10th cycle).…”
Section: Cinchona Catalysts – For Asymmetric Organocatalysismentioning
confidence: 99%
“…Among them, the use of DESs is probably the most promising alternative; according to the more accurate definition of DESs, they are eutectic solvents (eutectic-type systems that are liquid at a given desired temperature where at least one of its components would, otherwise, be a solid) whose components (hydrogen bond donors (HBDs) and hydrogen bond acceptors (HBAs), Lewis or Brønsted acids and bases) present enthalpic-driven negative deviations from thermodynamic ideality [108]. DESs have been proven to be very useful not only for biopolymer processing [109][110][111][112] but also for many other uses [113][114][115][116], including the preparation of bioactive compounds trough catalytic procedures [117][118][119][120], due to their several notable advantages, including biodegradability, low toxicity, and easy, cost-effective, and solvent-free preparation from readily available natural sources [108]. In this sense, and to highlight this last aspect, the term NADESs (natural deep eutectic solvents) was coined some time ago [121,122].…”
Section: Introductionmentioning
confidence: 99%